SHIFT WORK IMPACT TO SYMPTOMS OF ANXIETY, DEPRESSION AND SLEEP QUALITY AMONG NURSES - Millere, Inga; Deklava, Liana; Skutele, Ineta; Millere, Elīna; Fokina, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Shift work is prevalent in service industries such as hospitals that provide 24-hour coverage. There is no common accepted definition of shift work, but usually shift work is defined as work hours that are scheduled outside daylight (6 am–6 pm) hours. Purpose of study is to compare quality of sleep, anxiety and depression among nurses working daily and shifts in Latvia. In this study 4 research tools were used: a demographic questionnaire, Beck depression survey (BDI), The State-Trait Anxiety Inventory (STAI) and Pittsburgh sleep quality index (PSQI). Research results showed that nurses in shifts have higher mean value scores than day time working nurses in all indicators – depression, anxiety and sleep quality. This research is meaningful due to the fact that it allows to acknowledge and evaluate the role of shift work on nurses health particularly on mood disorders and sleep quality.